The Effectiveness of English Songs to Improve Students’ Pronunciation of Single Vowels in English Words for EFL Students - Kadir, Nurlaily Rahmadhany (RETAIN, 2022)
Indonesia is the country where English is positioned as a foreign language. As a foreign language, English is familiar to Indonesian students. Although they have learnt it, they still get many difficulties in learning this language. They also have difficulties to pronounce English words. The correct pronunciation becomes one of the main that are important in communication using English. Thus, the researcher realized that was very useful to make and help the students practiced pronunciation through such interesting activity as often as possible by using some attractive strategy or interesting medias. The researchers chose song especially English songs as one of the media to teach and help the students to pronounce English words well. This present research investigated the effectiveness of English songs in teaching pronunciation especially the pronunciation of single vowels for secondary EFL students. It was a quantative research that used experimental design. This study was conducted on secondary EFL students in Senior High School in the tenth grade (X MIPA 1 as an experimental group and X MIPA 2 as a control group) at one of Public Senior High School in Sidoarjo. The researcher gave pre-test and post-test for those classes and the treatment would be given to the experimental group, while the control group would be taught with no treatment. First, the researcher gave pre-test to both of the group in order to make sure that both groups were equal.in the end of the research, the researcher conducted post test for those classes in order to know whether there would be any significant effect of students pronunciation in single vowels. The researcher analyzed the data by using Wilcoxon Test, using IBM SPSS for Windows release 24. The finding of this research revealed that English songs were effective in teaching English to improve students’ pronunciation of single vowels in English words for EFL students.Keywords: English song, pronunciation, single vowel.